Search costs, sorting and "property ladder" effects: Evidence from the valuation of amenities - Ronan Lyons (European Regional Science Association (ERSA), 2012)
The housing market is one of the most important markets in any economy, constituting typically both the most important class of consumption good and the most widely held investment asset. The origin of the Great Recession in the U.S. housing market has shown the importance of linkages between housing and the wider economy. Yet not only are these links poorly understood, so too are the mechanics of the housing market itself. Property-specific attributes aside, the housing market is an inherently spatial one, with location choice and price determined by bundles of amenities. This paper examines four issues related to understanding housing markets and their cycles. To do so, it uses a rich dataset of one million property listings in Ireland, from the end of bubble in 2006 to 2011, by which time property prices had halved. The dataset covers not only bubble and crash periods, but also sales and lettings segments and urban and rural markets. It finds, firstly, that over twenty location-specific amenities, in five broad categories from environmental to market depth, are reflected in costs of accommodation. Signs are in accordance with expectations, once congestion and flooding effects for certain amenities are considered. Secondly, it investigates whether amenities are subject to Tiebout-style sorting and income elasticities. It finds that the price of most amenities is indeed amplified in urban markets. Thirdly, it exploits coverage of both sales and lettings segments to investigate whether the relative valuation of amenities differs between prices and rents. It finds that typically there is a greater valuation of amenities in the sales segment than in lettings. This is indicative of either indivisibilities related to tenant search costs or a desire on the part of buyers to lock in access to amenities. Such lock-in concerns would be reflected in procyclical amenity prices. The final contribution of the paper is an investigation of whether amenity valuations vary with the market cycle. While there is no one clear overall picture from the amenities included, there is more evidence in favour of countercyclical amenity prices, a "property ladder" effect, than procyclical prices and the desire to lock in access to amenities.
Keywords: R31; E32; H4; D62; H23; 330; Housing markets; amenity valuation; income sorting; search costs; market cycles